Cellular Proliferative Response to Cardiac Troponin‐I in Patients with Idiopathic Dilated Cardiomyopathy - Lappé, Jason M. (Blackwell Publishing Inc, 2011)
Background: Approximately 20% of patients with idiopathic dilated cardiomyopathy (iDCM) have autoantibodies (AAbs) specific to cardiac troponin‐I (cTnI). However, there has been no work evaluating active cellular autoimmunity. We aimed to identify a cTnI‐stimulated cellular autoimmune response and to correlate our findings with cTnI AAb production. Methods: Samples were obtained from stable ambulatory iDCM patients and healthy controls. Peripheral blood monocytes were incubated with cTnI, and cellular proliferation was measured using flow cytometry. AAbs against cTnI were detected by enzyme‐linked immunosorbent assay. Results: A positive cellular proliferative response to cTnI was identified in 20.5% (9/44) patients with iDCM and 5.7% (2/35) of healthy controls (p < 0.05). Positive cTnI AAbs were identified in 20% (7/35) of healthy controls and 13.6% (6/44) of patients with iDCM (p = NS). The presence of cTnI AAbs did not correlate with a positive cellular proliferative response. However, patients with iDCM who had an AAb response to cTnI were less likely to be taking a statin (p < 0.05). Conclusions: A cellular autoimmune response to cTnI is demonstrated in a subset of patients with iDCM. However, the presence of a cellular response did not correlate with the presence of AAbs to the same antigen. Clin Trans Sci 2011; Volume 4: 317–322